Varicella-zoster meningovasculitis in a multiple sclerosis patient treated with natalizumab. (March 2018) - Mulero, Patricia; Auger, Cristina; Parolin, Laura; Fonseca, Elena; Requena, Manuel; Rio, Jordi; Tintoré, Mar; Rovira, Alex; Montalban, Xavier
Background: Natalizumab is associated with the occasional occurrence of progressive multifocal leukoencephalopathy (PML). While natalizumab-associated PML is well described in multiple sclerosis (MS) patients, herpes and other infections have rarely been reported. Objective: To report a case of varicella-zoster (VZV) meningovasculitis in a MS patient treated with natalizumab. Methods: Case report. Results: A 48-year-old woman diagnosed with MS in treatment with natalizumab (Expanded Disability Status Scale (EDSS): 4.0). After 72 infusions, she complained of a holocraneal headache and a new unsteady gait with diplopia (EDSS: 5.0). A brain and spinal cord magnetic resonance (MR) scan showed a multifocal leptomeningeal enhancing nodular lesions and an angiography revealed irregularity of the proximal segments of cerebral arteries. Testing for VZV DNA by polymerase chain reaction (PCR) amplification was positive in cerebrospinal fluid. Treatment with endovenous acyclovir was started. After clinical improvement (EDSS: 4.5), treatment with natalizumab was restarted associated with oral acyclovir as prophylaxis. Conclusion: Neurologists should be aware of other possible neuroinfections besides PML in MS patients under natalizumab.